Effect of Transition Metals on the Oxygen Reduction Reaction Activity at Metal‐N3/C Active Sites. Issue 1 (6th November 2020) - Fruehwald, Holly M.; Ebralidze, Iraklii I.; Zenkina, Olena V.; Easton, E. Bradley
Abstract: The roles of various transition and post‐transition metals in model non‐precious‐metal catalysts for the oxygen reduction reaction (ORR) are reported after being prepared via a molecularly defined terpyridine unit covalently attached to a carbon black support. We previously reported the use of a terpyridine‐modified iron‐based catalyst that allowed for the controlled deposition of highly active nitrogen functionalities on the carbon support, which adopts a Fe−N3 /C active site formation. In this work, we expand on this idea by altering the metal center in the predefined active sites M−N3 /C and compare the ORR reactivity of the isostructural set of catalysts, where M=Fe, Co, Ni, Mn, and Sn. The results show that the iron‐based material was the most active catalyst in acid, whereas the cobalt‐based catalyst was most active in base. In addition, nickel‐ and manganese‐based materials showed promising activity for the ORR in both acidic and basic media. We demonstrate that, with a suitable templating bis‐chelating nitrogenous ligand, the M−N3 /C active site geometry is adopted with a wide range of non‐precious‐metal centers on a Vulcan carbon surface, and the resulting catalysts are ORR active in a range of conditions, further confirming the tunability and versatility of the N3 site. As expected, post‐transition metals, such as tin, do not coordinate to the N3 nitrogenous ligand under synthetic conditions and deposits tin oxides(s). This study confirms the generality of the phenomenon of M−N3 /C as an ORR catalytic site. Abstract : What role does the metal play in M‐N3 /C active site ? Using a terpyridine‐based molecular receptor, the surface of the carbon support can be modified with highly active pyridinic nitrogen. This active site does not require further heat treatment to improve activity. Using similar methodology, the N3 /C site is used to assess the effect of altering the metal center, using transition and post‐transition metals, in terms of the activity for the oxygen reduction reaction (ORR). Transition metals have good activity in the N3 /C site for the ORR in acid and base, whereas post‐transition metals show some activity but do not coordinate to the active site. N3 /C can host a variety of transition metals while maintaining high activity for the ORR.